2009
DOI: 10.1073/pnas.0812530106
|View full text |Cite
|
Sign up to set email alerts
|

IL-9 induces differentiation of T H 17 cells and enhances function of FoxP3 + natural regulatory T cells

Abstract: The development of T helper (TH)17 and regulatory T (Treg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
394
5
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 437 publications
(428 citation statements)
references
References 35 publications
23
394
5
6
Order By: Relevance
“…Moreover, it has also been shown that IL-9 synergizes with TGF-beta1 to differentiate naive CD4 + T cells into Th17 cells and postulated an additional role for IL-9 in mediating the suppressive function of Tregs in experimental autoimmune encephalomyelitis. 38 Thus, our microarray data are coherent with these findings and provide further support for the importance of IL-27 and IL-9 cytokine signalling in the development of T1D.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, it has also been shown that IL-9 synergizes with TGF-beta1 to differentiate naive CD4 + T cells into Th17 cells and postulated an additional role for IL-9 in mediating the suppressive function of Tregs in experimental autoimmune encephalomyelitis. 38 Thus, our microarray data are coherent with these findings and provide further support for the importance of IL-27 and IL-9 cytokine signalling in the development of T1D.…”
Section: Discussionsupporting
confidence: 84%
“…These results changed our perception of the IL-9 stimulating activity of TGF-b/IL-4 reported by Schmitt [11]. More recently, still, IL-9 production by CD4 1 T cells stimulated in the presence of TGF-b/IL-6, the canonical Th17 combination [12][13][14], was also reported [15,16].…”
Section: Introductionmentioning
confidence: 58%
“…Several publications have reported IL-9 production by purified Th17 CD4 1 T cells activated with anti-CD3/CD28 [15,16]. We carefully tested this condition in antigen recall responses of mice immunized with OVA.…”
Section: Introductionmentioning
confidence: 99%
“…However, the net effect of IL-9 depends on the cellular context. There are hints that IL-9 may act directly on Tregs (which express IL-9Ra), enhancing their suppressive function and indirectly on Th17 cells (which do not express IL-9Ra), promoting their proliferation and/or accumulation [98]. IL-9 induces the expression of the chemokine CCL20 by astrocytes, which enhances the migration of Th17 cells into the CNS.…”
Section: Il-9mentioning
confidence: 99%